Hastags and Digital Mobilization Movements (DMO): Communication Network Analysis on #BubarkanPOLRI vs #Polripresisi Hastags on Twitter Social Media - Leo Nando Sastro; Daniel Susilo; Teguh Dwi Putranto (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
This study examines the role of hastags (#BubarkanPOLRI) that first appeared during the Buaya vs Cicak incident where the KPK wiretapped case against the Kabareskrim Mabes Polri which was allegedly involved in disbursing funds from Bank Century customers. Hastag (#BubarkanPolri) Reappeared during the riots at the Kanjuruhan Malang stadium as quoted from the @akmalmarhali20 account